Repeated detection of H7N9 avian influenza viruses in raw poultry meat illegally brought to Japan by international flight passengers - Shibata, Akihiro; Okamatsu, Masatoshi; Sumiyoshi, Riho; Matsuno, Keita; Wang, Zu-Jyun; Kida, Hiroshi; Osaka, Hiroyuki; Sakoda, Yoshihiro (Virology (New York, N.Y.), 2018)
H7N9 highly and low pathogenic avian influenza viruses (HPAIV and LPAIV, respectively) have been isolated from duck meat products that were brought illegally into Japan by flight passengers in their hand luggage. These H7N9 virus isolates were phylogenetically closely related to those prevailing in China. Antigenic analysis revealed that the hemagglutinin of the H7N9 HPAIV isolate was slightly different from those of the H7N9 LPAIV and older H7 strains. These meat products contaminated with AIVs repeatedly brought into Japan lead to increased risks of poultry and public health. Continuous border disease control based on the detection and culling of infected poultry and meat products is, thus, essential for the prevention of introduction and spread of AIVs.